IMPLIKASI KECANDUAN DALAM PERSPEKTIF PSIKOLOGIS PEREMPUAN PADA PROSES PENANGANAN PENYALAHGUNAAN NARKOTIKA (NOURA: Jurnal Kajian Gender dan Anak, 2022)
Narcotics are dangerous goods because they can change a person's personality for the worse and can also change the nervous system which has a negative impact on the wearer, especially women. Narcotics are included in criminal acts that can damage morals and psychology. As for narcotics, both users and owners of drug distribution have been regulated in the Law of the Republic of Indonesia Number 22 of 1997. Most Indonesian people, especially women, have increasingly complex needs as a result of the lack of communication between their families and economic problems causing them to be trapped in a snare. drugs. Narcotics abuse by women will have bad implications for their lives, especially it will greatly affect their physical, psychological development, and even their daily behavior. But with a very strong psychological urge or curiosity to have the illicit goods. So that addiction to narcotics can have psychological symptoms for women. Which of these symptoms has something to do with social phenomena, giving rise to effects in the form of encouragement to become parents' backgrounds, taking other people's things, being possessive, manipulative, and so on. If the abuse of narcotics is not immediately addressed, it will have a big impact. Because it will be a trigger for the destruction of millennials as the successor to the younger generation who were initially active and intelligent, but after the advent of narcotics, they changed their thinking to nothing, especially women. The purpose of this study is to find out how the impact in the perspective of women's psychology on the process of handling narcotics abuse. This study only discusses drug abuse in women and the rampant circulation of drugs and the causes and impacts that occur when women are addicted to narcotics. In this case, the handling that needs to be done is through training efforts to empower women both socially and economically.Keywords: Implications, Addiction, Handling, Women's Psychology, Narcotics